Pengaruh Pengumuman Undang-Undang Perpajakan Tahun 2000 Terhadap Harga Saham - Sylvie Ayuningtyas; Wirawan ED Radianto (Jurnal Riset Manajemen dan Bisnis, 2006)
Tax regulation in lndonesia hos been changed for several times. The purpose is to stimulate basiness in Indonesia so that it will increase national income. One of the main purpose of Tax Reform 2000 is to increase companies' efficiency. As a result it wilt maximize companies' value through stabilizing and increasing stork capitalization. The aim of this research is to investiate whetlter tax reform announcement influence stock price, klown as abnormal return. Data is gathred from Jakarta Stock Exchange and samplewas manufactured indutries. The resesrch showed that there was abnormal returned for several days arround tax reform announcementKey words: Tax regalation, stock price, abnormal return.